Опосредованность интуитивного синтетического суждения - Бардин, Александр Николаевич (НТУ "ХПИ", 2016)
Для познания мира – и физического и духовного – совершенно необходимы два существенно различных метода: с одной стороны, дискурсивный, логический, с другой – интуитивный, т.е. непосредственное синтетическое суждение, не опирающееся на доказательство, причем этот второй метод, с точки зрения гносеологической, в основе своей один и то же в науке и в искусстве, в вопросах физики и этики. Опыт всегда ограничен, и суждение о его достаточности, о доказательности – есть внелогический акт, в полной мере интуитивный, не сводимый логически к другим положениям, принятым за основные и безусловно верные. Подтверждение предсказаний укрепляет убедительность суждения.

For word cognition as physical, so spiritual it is important to use two different methods: logical and intuitive that is direct synthetic judgment, which is not based on proof. This method gnoseologicaly is the same as in science and art go in physics and ethics. The experience is limited and the measuring about its enough and grounded character is the out-logical act, fully intuitive, which can’t be reduced logically to the other statements accepted as basic and undoubtedly true. The realization of forecasts keeps statements persuasive. To prove true and persuasive character of intuitive syntethetive judgment in any area it is important to use two criterions: practical citation and sense of satisfaction, inner persuasion. However, to be real critension of truth such satisfaction, persuasion must realize definite conditions. So the judgment must be general. it must not be used for the interests of the one into makes the judgements.
Mediation intuitive synthetic judgment
Keywords: интуиция; логика; метод; практика; правда; intuition; synthetic judgement; logic; method; practice